2022
DOI: 10.3390/polym14030599
|View full text |Cite
|
Sign up to set email alerts
|

PVP/Highly Dispersed AgNPs Nanofibers Using Ultrasonic-Assisted Electrospinning

Abstract: Silver nanoparticles (AgNPs) are novel materials with antibacterial, antifungal, and antiviral activities over a wide range. This study aimed to prepare polyvinylpyrrolidone (PVP) electrospinning composites with uniformly distributed AgNPs. In this study, starch-capped ~2 nm primary AgNPs were first synthesized using Atmospheric pressure Pulsed Discharge Plasma (APDP) at AC 10 kV and 10 kHz. Then, 0.6 wt.% AgNPs were mixed into a 10 wt.% PVP ethanol-based polymer solution and coiled through an Ultrasonic-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…This result of color changes was in agreement with a previous study reported by Khan et al [ 19 ]. UV-Vis spectroscopy showed a unique SPR absorption band at around 400 nm, typical in AgNPs, and indicated that the particles were dispersed without aggregation [ 20 ]. The XRD pattern of AgNPs confirms the crystallinity with a face-centered cubic (FCC) plane ((JCPDS, File No.…”
Section: Discussionmentioning
confidence: 99%
“…This result of color changes was in agreement with a previous study reported by Khan et al [ 19 ]. UV-Vis spectroscopy showed a unique SPR absorption band at around 400 nm, typical in AgNPs, and indicated that the particles were dispersed without aggregation [ 20 ]. The XRD pattern of AgNPs confirms the crystallinity with a face-centered cubic (FCC) plane ((JCPDS, File No.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Jebril et al [51] reported the efficacy of Melia azedarach leaf extract to synthesize AgNPs at an SPR value of around 400 nm. This obtained peak (400 nm) is typical for AgNPs and demonstrates that the particles were evenly distributed without clumping together [52]. As indicated in numerous research investigations, the SPR wavelength for silver nanoparticles (AgNPs) produced through biological synthesis falls within the range of 400-450 nm.…”
Section: Discussionmentioning
confidence: 53%
“…The dye decomposition rates of methylene blue under different pressures are listed in Table 1 from which it can be observed that the rates were low. According to our previous study, 21 the concentration of reactive species generated by plasma increases with an increase in the number of electrodes. Therefore, the number of electrodes was increased to seven, including three ground electrodes and four high-voltage electrodes (Figure 3b).…”
Section: Resultsmentioning
confidence: 65%
“…This system provides an easy, continuous, and environmentally friendly process and has been applied successfully for the decomposition of methyl blue 19 and synthesis of silver nanoparticles 20 and cerium dioxide nanoparticles. 21 However, this system has only been applied under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%